2011
DOI: 10.1074/jbc.m111.218065
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-like 1 Knock-out Mice (Cytl1−/−) Show Normal Cartilage and Bone Development but Exhibit Augmented Osteoarthritic Cartilage Destruction

Abstract: We have shown that cytokine-like 1 (Cytl1) is a novel autocrine regulatory factor that regulates chondrogenesis of mouse mesenchymal cells (Kim, J. S., Ryoo, Z. Y., and Chun, J. S. (2007) J. Biol. Chem. 282, 29359 -29367). In this previous work, we found that Cytl1 expression was very low in mesenchymal cells, increased dramatically during chondrogenesis, and decreased during hypertrophic maturation, both in vivo and in vitro. Moreover, exogenous addition or ectopic expression of Cytl1 caused chondrogenic diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 23 publications
(55 reference statements)
2
54
0
Order By: Relevance
“…However, CCL2 could also reportedly inhibit development of colitis and colorectal cancer by exerting inhibitory effects on lymphocytes in disease models in mice (45). A study by Chun and colleagues (11) reported that Cytl1 2/2 mice were more sensitive to osteoarthritic cartilage destruction, which indicated that CYTL1 might have an anti-inflammatory effect. Indeed, Chao et al (12) demonstrated that CYTL1 could significantly reduce acute joint inflammation in a murine arthritis model and block expression of several key inflammatory genes such as IL-1b and IL-6 in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CCL2 could also reportedly inhibit development of colitis and colorectal cancer by exerting inhibitory effects on lymphocytes in disease models in mice (45). A study by Chun and colleagues (11) reported that Cytl1 2/2 mice were more sensitive to osteoarthritic cartilage destruction, which indicated that CYTL1 might have an anti-inflammatory effect. Indeed, Chao et al (12) demonstrated that CYTL1 could significantly reduce acute joint inflammation in a murine arthritis model and block expression of several key inflammatory genes such as IL-1b and IL-6 in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Chun and colleagues (10,11) determined that Cytl1 2/2 mice were more sensitive to osteoarthritic cartilage destruction. Chao et al (12) demonstrated that CYTL1 could significantly prevent inflammatory arthritis.…”
mentioning
confidence: 99%
“…Dkk-2 expression in Col2a1-Dkk2-transgenic mice was also decreased after DMM surgery, but Dkk-2 expression still remained at a relatively high level compared with that in WT mice ( Figures 5B and C). We have previously shown that type II collagen expression is decreased in OA cartilage destruction caused by DMM surgery (32), suggesting that the promoter activity of Col2a1 in transgenic mice may be reduced in DMM-induced OA cartilage destruction. Therefore, the decrease of Dkk-2 expression in trans- Dkk-1 INHIBITS EXPERIMENTAL OAgenic mice may be due to the nature of the Col2a1 promoter and enhancer that we used to generate transgenic mice.…”
Section: Dkk-1 Inhibits Experimental Oamentioning
confidence: 97%
“…(18) PCR primers and conditions are shown in Supplemental Table 1. Cartilage and skeletal staining, histological analysis, immunohistochemistry, and immunofluorescence microscopy Cartilage and skeletons of whole-mouse embryos or postnatal mice, and mineralized zones in developing bone were stained with alcian blue, alizarin red, and von Kossa. (19) The lengths of bone and mineralized zones were measured using the AxioVision microscope image analysis program (Carl Zeiss, Jena, Germany). CD31, Vegf, Mmp9, Dkk1, Dkk2, and RANKL (receptor activator of nuclear factor kB ligand) in cartilage or bone sections were detected by immunofluorescence microscopy or immunohistochemical staining.…”
Section: Animalsmentioning
confidence: 99%